The Effect of Parental Environment Quality and Participation in Early Childhood Education on Children's Character - Mustika - Dewanggi; Dwi - Hastuti; Tin - Herawati (Department of Family and Consumer Sciences, Bogor Agricultural University, 2016)
This study aims to analyze the effect of parental environment quality and participation in early childhood education on children's character. A sample in this study was randomly selected (random sampling) involving 100 respondents. Data were collected through interviews and observation techniques with the help of questionnaires. Data were analyzed with descriptive analysis, independent t-test, and regression test. The results showed that parental environment quality in which their children did not attend early childhood education was better than that whose children attended early childhood education. The results showed that there was a significant effect of parental environment quality on children’s character, and there was no significant effect of participation in early childhood education on children's character.